Por uma percepção mais ampla da “nova” vitimologia dentro do Processo penal ordinário. - Vasconcelos, Larisse Salvador Bezerra de (2018)
The present study aims to address the maintenance of the problematic of the victim within the criminal process, regarding its annulment and the inexpressiveness of system responses directed especially to the victim, even in the face of the paradigms brought by the "New" Victimology - here identified as being Victimology which has its references related to Human Rights and Critical Criminology - and criminal procedural instruments that would serve the victim's participation, attention and integration within the criminal process. The question of forgetting the victim within the criminal process, although it is a point of reiteration of victimized speeches over the years, becomes essential for discussion and analysis of the complex structure of the criminal phenomenon and the spread of violence in a postmodern society more and more interconnected and globalized, since it is understood that the annulment of the victim by the punitive structure of the state, besides leading to the realization of secondary victimization, is deposed against the system itself, and it is disqualified. Consequent to the idea presented it is necessary to overcome the criminal ideology that presupposes the necessary removal from the victim in order to ban private revenge. Once the evolution of victim thinking has been identified, through a bibliographical research, from its classic matrix to its connection with Critical Criminology, as well as pointed out the current criminal procedural instruments that would meet the desire to give relief to the victim within the process, to a documentary survey about the forensic reality regarding the use of such instruments through the study of a sample of sentences published by the Criminal Courts of Recife, through which it was possible to measure the application and effectiveness of these instruments. Thus, in view of the research carried out, one has the prospect of demonstrating that the ideals of "New" Victimology are immensely distant from the reality of the current system and that even procedural instruments that could give relief to the victim through the simple application of the norm , are rendered unusable and inexpressive. Finally, as a direct practical result of the research, obtaining data capable of critically analyzing Law nº. 8.045/ 2010 - which may establish a new Code of Criminal Procedure in the country - on the question of victimhood and, secondly, on the importance of Victimology in criminal proceedings, influencing the creation of legislation and the perception of the operators of the law.